2013
DOI: 10.1509/jim.12.0121
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization Knowledge: What, Why, Where, and When?

Abstract: The acquisition of relevant knowledge plays a critical role in the internationalization process. Yet a complete understanding of internationalization knowledge (IK) remains largely unexplored in the international marketing literature. The authors develop a framework that distinguishes three categories of IK necessary for internationalizing firms to gain market entry, localize strategies, and organize international enterprise procedures. Employing a longitudinal qualitative analysis often internationalizing fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 96 publications
3
88
0
2
Order By: Relevance
“…For example Bruneel et al (2010) found evidence that key exchange partner's internationalization impacts SMEs' internationalization propensity. Furthermore, Fletcher and Harris (2012) as well as Fletcher et al (2013) suggest that external consultants play a crucial role in transporting internationalization knowledge. This may fuel isomorphism of competitors (Ghoshal, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example Bruneel et al (2010) found evidence that key exchange partner's internationalization impacts SMEs' internationalization propensity. Furthermore, Fletcher and Harris (2012) as well as Fletcher et al (2013) suggest that external consultants play a crucial role in transporting internationalization knowledge. This may fuel isomorphism of competitors (Ghoshal, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the context of young and thus less experienced firms, Bruneel et al (2010) found evidence of a decreasing amount of outbound orientation with increasing amounts of international experiential knowledge. Likewise, Fletcher, Harris, and Richey (2013) suggest that firms are in need of internationalization knowledge and thus turn to external sources when they require an alternative mode of market entry rather than those they are already experienced with. Finally, Fletcher and Harris (2012) point to the high firm specificity of international knowledge and the central importance of internal international experience for SMEs in their course of internationalization.…”
Section: The Moderating Effect Of Experience On Imitation and Internamentioning
confidence: 99%
“…This actor is commonly internal to the firm (frequently the SME itself), while external actors remain under-researched. Specifically, advisers, although reported to have relevant internationalization knowledge, even more than could be obtained from network relationships (Fletcher & Harris, 2012;Fletcher et al, 2013), have been neglected by the SME internationalization literature.…”
Section: Knowledge As a Catalyst Of Sme Internationalizationmentioning
confidence: 99%
“…Yet, the SME internationalization literature largely focuses on internal actors, such as knowledge generated by a firm's managers and key employees, whereas to date, the voice of the advisers remains almost silent. Advisers are recognized as relevant sources of knowledge for internationalizing SMEs (Fletcher & Harris, 2012;Fletcher, Harris, & Richey, 2013). They can provide micromultinationals with crucial knowledge for their international operations.…”
mentioning
confidence: 99%
“…In accordance with this notion, various studies have suggested that interorganizational affiliations generate knowledge acquisition and operationalization prospects (Dyer and Singh 1998;Lane and Lubatkin 1998;Larsson et al 1998;Chetty and Holm 2000). Even though inter-organizational learning in a group setting has been viewed as essential for the successful operations of foreign companies, there is still a dearth of empirical qualitative studies scrutinizing the dynamics of learning in international business (Keupp and Gassmann 2009;Fletcher et al 2013). This gap is even deeper within the context of the assets of foreignness literature, which welcomes further insight on the dynamics of how firms operate within networks (Denk et al 2012).…”
Section: Introductionmentioning
confidence: 98%